'… The point is to change it' – Yes, but in what direction and how? Intellectual activism as a way of 'walking the talk' of critical work in business schools. (March 2018) - Contu, Alessia
This article is a call to embrace and work towards a specific form of intellectual activism in business schools. Based on the inspiring work of Professor Patricia Hill Collins and other Black feminist and post-colonial scholars, intellectual activism is here defined as 'the myriad ways in which people place the power of their ideas in service to social justice'. This article calls for and delineates a positive response to the current crisis by identifying key features and areas of work that scholars can engage with in 'walking the talk' of critical work in business schools.